Plasma glutamine levels in patients after non-elective or elective ICU admission: an observational study. Issue 1 (December 2015) - Buter, Hanneke; Bakker, Andries; Kingma, W.; Koopmans, Matty; Boerma, E.
Abstract Background A low plasma glutamine level at the time of acute admission to the intensive care unit (ICU) is an independent predictor of an unfavourable outcome in critically ill patients. The primary objective of this study was to determine whether there are differences in plasma glutamine levels upon non-elective or elective ICU admission. The secondary objective was to compare glutamine levels over time, and to determine correlations between glutamine levels and the severity of illness and presence of infection in ICU patients. Methods We performed a single-centre observational study in a closed-format, 22-bed, mixed ICU. Plasma glutamine levels were measured at admission and every morning at 6.00 a.m. during the ICU stay. We aimed to include at least 80 patients per group. The study was approved by the local Medical Ethics Committee. Results In 88 patients after elective surgery, the median plasma glutamine level at admission was significantly higher compared with that in 90 non-elective patients (0.43 mmol/l [0.33–0.55 mmol/l] versus 0.25 mmol/l [0.09–0.37 mmol/l], P  = 0.001). During the ICU stay, plasma glutamine levels remained significantly higher in elective patients than in non-elective patients. There was a significant correlation between the APACHE IV score and glutamine levels (R  = 0.52, P  < 0.001). Moreover, backward linear regression analysis showed that this correlation was independently associated with the APACHE IV score and the presence of infection, but not with the type of admission. Conclusions Plasma glutamine levels are significantly lower after non-elective admission compared with elective admission to the ICU. A considerable amount of elective and non-elective patients have decreased plasma glutamine levels, but this is not independently associated with the type of admission. In contrast to previous studies, we found that plasma glutamine levels were determined by the severity of illness and the presence of an infection. Trial registration ClinicalTrials.gov, numberNCT02310035 .